PROJECT ACTIVITIES IN THE SYSTEM OF ADAPTATION OF AGRICULTURAL ENTERPRISES TO CRISIS CONDITIONS - Водолазська, Оксана; Квітницький, Е.Е. (SWorldJournal, 2026)
The article examines project activity as a key element of the system of adaptation of agricultural enterprises to crisis and war conditions of operation. It is substantiated that the modern agricultural sector is characterized by a high level of risks cau